ALM OF THE POPULAR BANK IN MOROCCO: GOAL PROGRAMMINGAPPROACH - Ezouine driss (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
We propose agoal programming model specific to the popular bank in order to meet the objectives targeted by decision-makers while respecting the various business and regulatory constraints with minimization of deviations from objectives and to determine the optimal balance between profitability, the model is verified using data of the popular bankin Morocco year 2017.